Utilizing TikTok as a Means of Religious Learning at the Salafiyah Dawuhan Islamic Boarding School - Dwi Lisnawati; Nonny Rulisty Putri Sutikno; Arico Ayani Suparto (FKIP - Universitas Riau, 2026)
The rapid development of digital technology has encouraged Islamic educational institutions, including Islamic boarding schools, to adapt their learning and da’wah strategies through social media platforms. This study aims to examine how TikTok is utilized as a medium for Islamic religious learning at the Salafiyah Dawuhan Islamic Boarding School and to explore the meanings constructed by participants in its use. This research employs a qualitative approach with a phenomenological method to gain an in-depth understanding of participants’ experiences. Data were collected through in-depth interviews, observation, and documentation, and analyzed using data reduction, data display, and conclusion drawing, supported by triangulation techniques. The findings reveal that TikTok is utilized through live streaming of religious study sessions and short religious videos, enabling continuous and flexible access to learning beyond the physical classroom. Participants perceive TikTok not only as a communication platform but also as an extension of the pesantren learning environment. In addition, TikTok expands the reach of da’wah to a wider audience, although challenges such as limited digital literacy and the risk of misinformation remain. This study concludes that TikTok functions as a complementary learning medium that supports traditional learning practices while enhancing accessibility and engagement in religious education.